Transversal Polyphonies: A Reflection with Miguel D. Norambuena on Félix Guattari's Trip to Chile. - Varas, Paulina E. (Deleuze & Guattari Studies, 2019)
This article is based on a series of conversations with the social psychologist Miguel D. Norambuena regarding Félix Guattari's visit to Chile in 1991. The conversation deals with different events, ranging from the process of dictatorial repression in Chile with the political exile of Miguel D., experiences of intersection between Chilean revolutionary processes and the experiences of May 1968, as well as forms of production of subjectivity in the neoliberal scenario of the 1980s. Different tools for practical reflection take place in this dialogue, from the collective listening that David Cooper developed on the outskirts of Paris, Guattari's seminars at his home or the visits to the La Borde clinic, Guattari's trip to Chile and the publication of the books Cartografías del deseo (1989) and El devenir de la subjetividad (1998) in Chile. Finally, the experience of the Daily Life Clinic currently being developed by Miguel D. in Geneva is addressed as part of a process of subjective ecosophic creation.